Structural, optical and dielectric properties of PbS and ZnS nanoparticles synthesized via microwave irradiation - Nasir, Maharaz Mohammed (2018)
The solar energy harvesting technology can be achieved by using semiconductor nanomaterial including lead sulphide (PbS) and zinc sulphide (ZnS) nanoparticles. Therefore, the modification of various properties of PbS and ZnS nanoparticles can be achieved by controlling their size may provide an advantage in producing new materials with optimized properties for many applications including photovoltaic, solar cells and other photo-electronic devices. In microwave irradiation synthesis, the effect of power, irradiation time and the solvent choice can impact the nature of the reaction and are still a major problem in preparing a particular range of nanoparticle size. Hence, in this research, different particles sizes of ZnS and PbS are prepared by microwave irradiation method involving distilled water, ethylene glycol, ethylene alcohol and isopropanol as various solvents used. The concentration of the precursors of zinc and lead sources to sulphur source (1:1), the solvents quantity of 40 ml, power (300 W) and the irradiation time are fixed. The particles sizes were determined using Scherrer’s equation from XRD spectra and from transmission electron microscopy (TEM). The crystallite sizes of PbS synthesized in ethylene glycol, distilled water, ethylene alcohol and isopropanol ranged from 28.7 to 43.3 nm and their corresponding estimated optical band gaps ranged from 2.53 to 2.20 eV. For ZnS nanoparticles the crystallite sizes ranged from 8.2 to 13.0 nm and their corresponding optical band gaps ranged from 3.52 to 3.34 eV. The effect of irradiation time on optical and structural properties of PbS and ZnS nanoparticles was also investigated, a number of samples are obtained by varying the irradiation time from 10, 15, 45 and 50 min for both the two samples. The reactions carried out in a fixed concentration, power (200 W) and ethylene alcohol as solvent. The crystallite sizes of PbS nanoparticles ranged from 32. to 65.8 nm and their estimated optical band gaps values ranged from 2.41 to 1.60 eV. For ZnS nanoparticles, the average particle sizes in different irradiation time ranged from 7.9 to 87.01 nm and their corresponding optical band gaps ranged from 3.42 to 3.26 eV. The FESEM studies for ZnS nanoparticles showed the effect of irradiation time on morphology on each particles size of PbS and ZnS nanoparticles. The PVP/PbS and PVP/ZnS nanocomposites are synthesized in ethylene glycol solution in 10, 20 and 30 min irradiation time. The final products are characterized using FTIR, XRD and UV-VIS spectroscopy. The dielectric properties of the obtained different sizes of PVP/PbS nanocomposites (23.4, 28.7 and 52.4 nm) and PVP/ZnS (7.9, 13.0 and 64.9 nm) are analysed using impedance spectroscopy at constant temperature of 303 K and frequency range of 40 Hz to 1 MHz. The maximum value of AC conductivity of each size of PVP/PbS (52.4, 28.7, 23.4 nm) ranged from 9.56 x 10-6 down to 3.55 x 10-6 S/cm, while for PVP/ZnS (64.9, 13.0, 7.9 nm), the values ranged from 1.34 x 10-5 down to 7.21 x 10-6 S/cm. The corresponding values for the DC conductivity are also found. In this work, the values of electrical conductivities are decreased as the particle sizes of the samples reduced from 64.9 down to 7.9 nm for PVP/ZnS nanocomposites while from 52.4 down to 23.4 nm for PVP/PbS nanocomposites. The synthesized nanocomposites with particles sizes of 64.9 and 52.4 nm are considered to be the nanocomposites possessing the best particle sizes for the applications of electronic devices due to their excellent electrical conductivity as compared to other samples.